Cellular immune response of SARS-CoV-2 vaccination in kidney transplant recipients: a systematic review and meta-analysis - Udomkarnjananun, Suwasin; Gatechompol, Sivaporn; Leelahavanichkul, Asada; Kerr, Stephen J. (Frontiers in Immunology, 2023)
Background: Evidence has demonstrated inferior humoral immune responses after SARS-CoV-2 vaccination in kidney transplant recipients compared to the general population. However, data on cellular immune responses in this population has not been established.We searched MEDLINE, Scopus, and Cochrane database and included studies reported cellular immune response rates in kidney transplant recipients after receiving SARS-CoV-2 vaccines. Studies that reported factors associated with cellular immune responder or non-responder were also included. (PROSPERO:CRD42022375544) Results: From total 1,494 articles searched, 53 articles were included to the meta-analysis.Twenty-one studies assessed cellular immune response by interferon-γ enzyme-linked immunosorbent spot (IFN-γ ELISPOT), 22 studies used interferon-γ release assay (IGRA), and 10 studies used flow cytometric analysis. The pooled response rate after 2-dose (standard regimen) and 3-dose of vaccination was 47.5% (95%CI 38.4-56.7%) and 69.1% (95%CI 56.3-80.6%) from IFN-γ ELISPOT, 25.8% (95%CI 19.7-32.4%) and 14.7% (95%CI 8.5-22.2%) from IGRA, and 73.7% (95%CI 55.2-88.8%) and 86.5% (95%CI 75.3-94.9%) from flow cytometry. Recipients with seroconversion were associated with higher chance of having cellular immune response (OR 2.58; 95%CI 1.89-3.54). Cellular immune response in kidney transplant recipients were lower than in dialysis patients (OR 0.24; 95%CI 0.16-0.34) and general population (OR 0.10; 95%CI 0.07-0.14). Age and immunosuppressants containing tacrolimus or corticosteroid were associated with inferior cellular immune response.Conclusions: Cellular immune response after SARS-CoV-2 vaccination in kidney transplant recipients was lower than in dialysis patients and the general population. Age, tacrolimus, and